The Dzuko Valley : an Ecological Study - Karnatak, D. C. (Indian Forester, 1994)
The study is based on the visit of the Dzulo Valley by the Wildlife Wing of Manipur Forest Department for exploring it for the creation of a National Park. The valley, bordering Manipur and Nagaland states, presents a unique assemblage of fauna and flora which need protection by the government against human onslaught so as to preserve the rich germ-plasm in its ecological niche.